(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study analyzes the impacts of the work environment on a selected teaching personnel’s productivity. The objective of this study is to determine how the work environment affects the teaching personnel’s productivity and to come up with a recommendation based on the collected data. The fifty selected teaching personnel are from the courses of Bachelor of Science in Hospitality Management (BSHM), Bachelor of Science in Tourism Management (BSTM), Bachelor of Science in Business Administration (BSBA), Bachelor of Science in Office Administration (BSOA) and Bachelor of Science in Accountancy Information System (BSAIS) from the department of College of Hospitality, Tourism, Business, Accountancy and Management (CHBAM) at Bestlink College of the Philippines. Based on the data gathered on the respondents' demographic profiles, fifty-two percent of them are female. Based on the result of the collected data, it shows that work ambiance, a secured and safe workplace, a good support system from colleagues, an organization that promotes good values that lead to high performance, and an established technological system are the work environments that have a significant effect towards the productivity of teaching personnel. It also shows that creating a learning material, reporting to work on time, being able to submit the reports before the deadline, and having a strategic plan for presenting the lessons are the effects of a good work environment on teaching personnel’s productivity.